Les dynamiques identificatoires des enseignants d’EPS débutants : les ressorts d’une discipline scolaire au filtre des processus de subjectivation et d’individuation - Pablo Buznic-Bourgeacq; Benjamin Delattre (Éducation et Socialisation)
This article proposes to apprehend some particularities of the place and role of PE teachers in the education system questioning the identification dynamics of trainee PE teachers. It aims to grasp the way in which these young professors constituted themselves as a disciplinary subject and to better understand how their movements of subjectivation and individuation can account for some springs of the identity matrix of this discipline. The three case studies, carried out from interviews with a non-directive tendency, made it possible to draw three figures of the discipline, in which physical and sports activities have been able to play a role of adjuvant to existence, temporary space of detestation or life-saving support for socialization.